Design and characterization of poly (3-hydroxybutyrate-co-hydroxyhexanoate) nanoparticles and their grafting in whey protein-based nanocomposites. (January 2021) - Corrado, Iolanda; Abdalrazeq, Manar; Pezzella, Cinzia; Di Girolamo, Rocco; Porta, Raffaele; Sannia, Giovanni; Giosafatto, C. Valeria L.
Abstract: This work succeeded in the preparation of a nano-biocomposite material based on the use of poly-3-hydroxybutyrate-co-hydroxyhexanoate nanoparticles (PHBHHx-NPs) within a scaffold of whey protein (WP) based films. The experimental conditions for PHBHHx-NPs preparation by solvent-evaporation technique were set up, and the obtained NPs characterized. Dynamic light scattering analyses showed that PHBHHx-NPs are stable, exhibiting a zeta-potential value close to −40 mV and a Z-average size of 80 nm. Morphological characterization by transmission and scanning electron microscopy confirmed nanoparticle average dimensions. The addition of PHBHHx-NPs to WP-based films improved the mechanical properties of the derived bioplastics, producing more extensible materials preserving their mechanical resistance. The grafting of PHBHHx-NPs as material fillers also enhanced the film barrier properties towards O2, the permeability to both water vapor and CO2 remaining unaffected. Graphical abstract: Image 1 Highlights: Design of poly (3-hydroxybutyrate-co-hydroxyhexanoate) nanoparticles (PHBHHx-NPs). Evaluation of PHBHHx-NPs as nanofillers in whey-protein based films. Derived biocomposites with improved flexibility and reduced O2 permeability.